Circulating Tumor Cells in Gastrointestinal Malignancies: Current Techniques and Clinical Implications. (19th October 2009) - Lurje, Georg; Schiesser, Marc; Claudius, Andreas; Schneider, Paul Magnus
Abstract : Since their introduction more than 50 years by Engell, circulating tumor cells (CTCs) have been evaluated in cancer patients and their detection has been correlated with clinical outcome, in esophageal, gastric, and colorectal cancer. With the availability of refined technologies, the identification of CTCs from peripheral blood is emerging as a useful tool for the detection of malignancy, monitoring disease progression, and measuring response to therapy. However, increasing evidence suggests a variety of factors to be responsible for disease progression. The analysis of a single CTC marker is therefore unlikely to accurately predict progression of disease with sufficient resolution and reproducibility. Here we discuss the current concept of CTCs, summarize the available techniques for their detection and characterization, and aim to provide a comprehensive update on the clinical implications of CTCs in gastrointestinal (GI) malignancies.